Upaya Peningkatan Motivasi Dan Hasil Belajar Biologi Melalui Model Pembelajaran Cooperative Script Siswa Sma Negeri 1 Lahusa Tahun Pelajaran 2024/2025 - Festina Lase; Jun Mardin Telaumbanua (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
Low learning motivation is often the root of the problem of suboptimal student learning outcomes, a condition also found in SMA Negeri 1 Lahusa. This study aims to describe the improvement of learning quality, motivation, and learning outcomes in Biology through the application of the Cooperative Script learning model. Using a Classroom Action Research (CAR) design, this research was conducted in two cycles on 29 students of Class XI-MIPA-3. Data were collected through observation sheets, questionnaires, learning achievement tests, and interviews, then analyzed quantitatively descriptively. The findings showed a significant increase in all observed variables. In Cycle I, learning quality and learning motivation only reached 64.70% and 67.31% respectively with the